Structure and Argument in Augustine’s Nativity Sermon 188 - Neer, Joost van (Augustinianum, 2014)
A thread runs through Augustine’s s. 188 that first moves from the spiritual realm via the physical realm to man, and then from man via the physical realm to the spiritual realm. This descending and ascending movement is a perfect depiction of God’s plan with man, which is to become humble himself in order to exalt man. The traditional division of s. 188 ignores the high level of symmetry that one finds in the sermon, and consequently obscures its splendid balance. It is not a help to the reader, but an obstacle. This article has therefore proposed a different solution: a division in three parts.